Phage Therapy: Consider the Past, Embrace the Future - Wei, Junwei; Peng, Nan; Liang, Yunxiang; Li, Keke; Li, Yingjun (Applied sciences, 2020)
Antibiotic-resistant bacteria infections pose a threat to public health. Considering the difficulty in developing new antibiotics, it is an urgent need to develop alternative therapies against bacterial pathogens. Bacteriophages (phages) are evaluated as potential substitutes or adjuncts of antibiotics because they are abundant in nature and could specifically lyse bacteria. In this review, we briefly introduce phage therapy and its advantages compared with traditional antibiotic therapy. We also summarize new emerging phage technologies, such as CRISPR-Cas, synthetic phages, etc., and discuss some possible obstacles and potential risks in the application process. We believe that, with the advancement in synthetic biology and delivery technology, phage therapy has broad prospects in the future.